Pengembangan Aplikasi Sembol sebagai Solusi Distribusi Sembako Berbasis Teknologi Digital - Supina Batubara; Eko Hariyanto; Abdul Khaliq; Afdi Afandi (Jurnal Nasional Teknologi Komputer, 2025)
Distribution of basic necessities (nine basic commodities) efficiently and evenly is a major challenge amidst the increasing needs of urban communities. The development of digital technology offers innovative solutions to overcome this problem, one of which is through e-commerce-based applications. This study aims to design, develop, and implement the Sembol application as an integrated basic necessities distribution platform. This application is designed to provide easier, faster, and safer access for consumers, as well as offer an efficient distribution mechanism for basic necessities suppliers and retailers. The methodology used includes user needs analysis, user-friendly interface design, and system testing to ensure application stability and performance. Case studies were conducted in urban areas with high populations to measure the impact of Sembol implementation on the effectiveness of basic necessities distribution. The results of the study showed that the Sembol application was able to increase distribution efficiency by up to 35% compared to conventional methods, reduce logistics costs, and increase user satisfaction. In conclusion, technological innovation through the Sembol application has the potential to be a sustainable solution in the basic necessities supply chain in the digital era, while also supporting increased accessibility of basic necessities for the wider community.